Mechanism of Neural Regeneration Induced by Natural Product LY01 in the 5×FAD Mouse Model of Alzheimer’s Disease - Li, Xiao-Wan; Lu, Yang-Yang; Zhang, Shu-Yao; Sai, Ning-Ning; Fan, Yu-Yan; Cheng, Yong; Liu, Qing-Shan (Frontiers in Pharmacology, 2022)
Background: A sharp decline in neural regeneration in patients with Alzheimer's disease (AD) exacerbates the decline of cognition and memory. It is of great significance to screen for innovative drugs that promote endogenous neural regeneration. Cytisine N-methylene-(5,7,4′-trihydroxy)-isoflavone (LY01) is a new compound isolated from the Chinese herbal medicine Sophora alopecuroides with both isoflavone and alkaloid characteristic structures. Its pharmacological effects are worth studying. Objective: This study was designed to determine whether LY01 delays the cognitive and memory decline in the early stage of AD and whether this effect of LY01 is related to promoting neural regeneration. Methods: Eight-week-old 5×Familial Alzheimer’s Disease (5×FAD) mice were used as disease models of early AD. Three doses of LY01 administered in two courses (2 and 5 weeks) of treatment were tested. Cognition, memory, and anxiety-like behaviors in mice were evaluated by the Morris water maze, fear conditioning, and open field experiments. Regeneration of neurons in the mouse hippocampus was observed using immunofluorescence staining. The effect of LY01 on cell regeneration was also demonstrated using a series of tests on primary cultured neurons, astrocytes, and neural stem cells (NSCs). In addition, flow cytometry and transcriptome sequencing were carried out to preliminarily explored the mechanisms. Results: We found that LY01 reduced the decline of cognition and memory in the early stage of 5×FAD mice. This effect was related to the proliferation of astrocytes, the proliferation and migration of NSCs, and increases in the number of new cells and neural precursor cells in the dentate gyrus area of 5×FAD mice. This phenomenon could be observed both in 2-week-old female and 5-week-old male LY01-treated 5×FAD mice. The neuronal regeneration induced by LY01 was related to the regulation of the extracellular matrix, associated receptors, and the S phase of the cell cycle. Conclusion: LY01 increases the proliferation of NSCs and astrocytes and the number of neural precursor cells in the hippocampus, resulting in neural regeneration in 5×FAD mice by acting on the extracellular matrix and associated receptors and regulating the S phase of the cell cycle. This provides a new idea for the early intervention and treatment of AD.